INTEGRASI MATERI PENDIDIKAN AGAMA ISLAM TERHADAP ILMU-ILMU RASIONAL DI SEKOLAH MENENGAH PERTAMA - HERNI ALISKA (STIT DARUL ULUM KOTABARU, 2022)
Religion and rationality are two perspectives that have a strong influence. Humans view religious values ​​and rational values ​​as different entities, causing a dichotomy paradigm, especially in the realm of education. However, educational institutions need to integrate religious education materials, especially Islam in providing rational values ​​to junior high school students. This study aims to analyze the application of Islamic religious education material in rational values ​​for junior high school students. The research method used is literature study. The results show that the integration of PAI material into rational science at the philosophical level must already be contained in the vision and mission to become a superior school in the aspects of science, technology, faith, and piety; at the material level, PAI was found for social sciences, natural sciences, mathematics, and citizenship; at the level of learning strategies, teachers quote verses from the Qur'an, hadith, and their interpretations on the stage of the rational science learning learning process which has an impact on increasing students' creative, innovative, critical thinking skills, and learning motivation. This integration also broadens the understanding that Islam is a source of knowledge and rational values ​​as described in the Qur'an and hadith educating them to practice and contextualize their knowledge through attitudes and behavior at school, and in everyday life.